2020
DOI: 10.1016/j.joca.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages regulate the progression of osteoarthritis

Abstract: OA is now well accepted as a low-grade inflammatory disease affecting the whole joint. In addition to mechanical loading, inflammation (particularly synovitis), contributes significantly to OA. Synovial macrophages act as immune cells and are of critical importance in the symptomology and structural progression of OA. Activated macrophages are regulated by mTOR, NF-kB, JNK, PI3K/Akt and other signaling pathways, and are polarized into either M1 or M2 subtypes in OA synovial tissues, synovial fluid, and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
224
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(257 citation statements)
references
References 69 publications
5
224
0
3
Order By: Relevance
“…Monocyte adhesion to synovium tissue is an important phenomenon in OA pathogenesis [ 28 ]. However, nothing is known about the impact of resistin-enhanced VCAM expression and monocyte adhesion to synovium tissue in OA pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Monocyte adhesion to synovium tissue is an important phenomenon in OA pathogenesis [ 28 ]. However, nothing is known about the impact of resistin-enhanced VCAM expression and monocyte adhesion to synovium tissue in OA pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages activate an innate immune response in OA pathology and progression. Thus, the products of macrophages play a role in OA pathology and can be used to understand OA mechanism and therapeutic innovations [66].…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
“…Macrophages are hematopoietic stem cell-derived immune cells and have now been shown to play a prominent role in the progression of OA. Increasing evidence has demonstrated that overactivated macrophages promote the in ammatory microenvironment, increase the secretion of matrix metalloproteinases, inhibit the proliferation and viability of joint resident stem cells, and prevent cartilage repair [9][10][11]. Haraden et al reported that osteoarthritic macrophages highly expressed costimulatory factors such CD80 and CD86, which further initiated the adaptive immune response and induced expanded tissue injury [11,12].…”
Section: Introductionmentioning
confidence: 99%